Celecoxib inhibits cancer growth through cyclooxygenase 2 (COX2) independent pathways in HepG2 hepatocellular carcinoma - bardaweel, sana; Khlefat, Sara (Jordan Journal of Pharmaceutical Sciences, 2021)
Chronic inflammation has long been associated to carcinogenesis. Evidence has shown that nonsteroidal anti-inflammatory drugs (NSAIDs) may decrease the risk of certain types of cancer. In this study, we assessed the anti-proliferative effects of different NSAIDs against liver cancer using HepG2 cell line. In addition, we evaluated the combined effects of a selective COX2 inhibitor (Celecoxib) with chemotherapeutic drugs. The anti-proliferative and combined effects of COX2 inhibitors were evaluated by MTT assay. The effect of COX2 inhibitors on gene expression was assessed using real time PCR (RT-PCR). Also, the effect of COX2 inhibitors on colony formation was assessed through colony-formation assay. COX2 inhibitors treatment significantly inhibited the growth of HepG2 cells in a dose-dependent manner. The combined treatment of Celecoxib with either doxorubicin or raloxifene resulted in synergistic effects. In addition, Celecoxib treatment significantly reduced the expression of Bcl2 and VEGF genes in HepG2 cells, while the COX2 gene was not detected at all in HepG2 cell line suggesting that the anti-tumorigenic activity of Celecoxib is COX2 independent. Our results also revealed that COX2 inhibitors treatment significantly reduced the number and size of colonies formed by HepG2 cells.